Adaptive problem maps (APM): Connecting data dots to build increasingly informed and defensible environmental conservation decisions. (15th June 2022) - Mather, Martha E.; Dettmers, John M.
Abstract: Connecting individual datasets from different projects to each other and to decisions can help manager-researcher-administrator teams link existing information and adapt their environmental decision-making process as new information becomes available. Throughout their careers, environmental professionals often collect data on many individual projects that address similar sets of natural resource conservation problems. Consequently, the institutions, agencies, and organizations that employ these environmental professionals accumulate a large reservoir of project-specific information. However, opportunities to advance broader natural resource conservation goals are lost if individual projects and datasets are not integrated. Here we illustrate how adaptive problem mapping (APM) provides a framing and internal structure that charts relationships among pertinent information types, germane data sets, applicable concepts, and relevant decisions. In the APM process, appropriately defined problem statements and coordinated bridging questions connect data and concepts to build a network of increasingly informed and defensible decisions. Although APM can be applied to many environmental problems, we focus on examples from aquatic systems in which fish are conservation priorities. Prioritizing an initial evaluation and regular modification of the relationships among datasets and decisions using the APM process helps manager-researcher-administrator teams envision, track, and update what is known, unknown, learned, and needed. The resulting broader point of view advances strategic planning, evaluations of progress, assessments of opportunity costs, identification of options, and justifications of decision-related actions. Highlights: Using adaptive problem mapping (APM) can advance strategic planning and evaluation. Connecting existing datasets to decisions improves environmental management. APMs are new pathways for integrating existing information for better decisions. APMs can be broadly applied across environmental problems. APMs help teams envision, track, and update what is known, unknown, or needed.